Phenotypic spectrum of hereditary neuralgic amyotrophy caused by the SEPT9 R88W mutation. Issue 1 (17th December 2009) - Ueda, M; Kawamura, N; Tateishi, T; Sakae, N; Motomura, K; Ohyagi, Y; Kira, J-i
Abstract : Background: Hereditary neuralgic amyotrophy (HNA), also known as hereditary brachial plexus neuropathy, has phenotypic and genetic heterogeneity. Mutations in the septin 9 ( SEPT9 ) gene were recently identified in some HNA patients. The phenotypic spectrum of HNA caused by SEPT9 mutations is not well known. Objective: To characterise the phenotype of a large family of HNA patients with the SEPT9 R88W mutation. Methods: We report clinical, electrophysiological, neuroimaging and genetic findings of six HNA patients from a Japanese family. Results: All 17 neuropathic episodes identified were selectively and asymmetrically distributed in the upper-limb nerves. Severe pain was an initial symptom in 16 episodes (94%). Motor weakness occurred in 15 (88%) and sensory signs in 10 (59%). A minor dysmorphism, hypotelorism, was seen in all. Nerve conduction studies revealed focal demyelination as well as prominent axonal degeneration changes. Needle electromyography revealed chronic neurogenic patterns only in the upper limbs. An MRI study showed a gadolinium-enhanced brachial plexus. The missense mutation c.262C>T; p.R88W was found in exon 2 of SEPT9 in all patients. Conclusions: The SEPT9 R88W mutation in this family causes selective involvement of the brachial plexus and upper-limb nerves. Wider and more universal recognition of clinical hallmarks and genetic counselling are of diagnostic importance for HNA caused by the SEPT9 mutation.